Antibiotic Availability and the Prevalence of Pediatric Pneumonia During a Physicians’ Strike - Ken Crocker; Benvon Cramer; James M Hutchinson (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Antibiotics are widely believed to be overpre-scribed for pediatric respiratory infections, yet there are few data available on the effect of a sudden decrease in antibiotic availability on pediatric infectious disease.